THE ROLE OF PUBLIC FINANCE IN ADDRESSING CLIMATE CHANGE CHALLENGES: BETWEEN POLICIES AND FINANCE-IN LIGHT OF THE NATIONAL DEVELOPMENT PLAN (2018-2022) - Dr. Rafeeq Abdul Razzaq Muhammad Al-Quraishi (Scholar Express Journals, 2025)
Imposes change climate Challenges intense Difficulty on The authors Policies . As well. Requires change climate Take action in all economic sectors And on level the society In its entirety . And it requires procedures Confrontation To change climate Coordination between Many from Owners interest on Government level And other Governmental . And given because phenomenon change climate to speak on bezel range My time long The term Then Confrontation For this The phenomenon Requires the presence of capacity on planning commitment trusted And its implementation And support it And achieve Its sustainability To achieve Policies ambitious extremely on bezel Many from Political cycles . And of course. It will be there gains And losses . And often. what It is done Objection on Policies same Relationship With this The matter
Keywords: Public finance; climate change; national development